1994
DOI: 10.1002/j.1552-4604.1994.tb03963.x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of 10% Pentastarch and 5% Albumin in Patients Undergoing Open‐Heart Surgery

Abstract: Colloids are useful in cardiac surgery to increase preload and improve cardiac output without the risks associated with blood transfusions. Pentastarch is a new low-molecular weight hydroxyethyl starch compound under investigation for this purpose. The authors compared, in a randomized fashion, 12 patients who received pentastarch and 17 patients who received albumin for volume expansion after open-heart surgery. During the 24-hour study period there was no significant difference between the two groups with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(11 citation statements)
references
References 12 publications
0
10
0
1
Order By: Relevance
“…Nonprotein colloids may be useful in reducing systemic edema. 7,14,15 Neonatal Hyperbilirubinemia Albumin should not be administered in conjunction with phototherapy or prior to exchange transfusion. Albumin has been used with mixed results as an adjuvant to exchange transfusion.…”
Section: Thermal Injurymentioning
confidence: 99%
“…Nonprotein colloids may be useful in reducing systemic edema. 7,14,15 Neonatal Hyperbilirubinemia Albumin should not be administered in conjunction with phototherapy or prior to exchange transfusion. Albumin has been used with mixed results as an adjuvant to exchange transfusion.…”
Section: Thermal Injurymentioning
confidence: 99%
“…Reports of bleeding abnormalities [12][13][14] and effects on renal function [15][16][17] by higher substituted HES and DEX have not been similarly reproduced in PTS, likely due to its lower substitution and MW. Several clinical studies have shown the efficacy and safety of PTS in critically ill patient populations including in pump priming during [18] and following [19,20] cardiac bypass, in burn patients [21], in sepsis [22,23] and in trauma [24,25]. While not available in the USA, PTS and other lowersubstituted, medium MW starches are used liberally in European and Canadian intensive care units to resuscitate various forms of shock.…”
Section: Introductionmentioning
confidence: 99%
“…Postoperatif kardiovasküler stabilitenin korunması amacı ile değişik sıvılar kullanılabilir. Postoperatif dönemde kullanılan sıvılarla ilgili olarak çok sayıda prospektif randomize çalışma vardır (20,(49)(50)(51) . Ancak, bu çalışmalardaki hasta sayılarının çok az olması (7 ile 20 arasında değişmekte), volüm replasmanı kriterlerinin tek tip (üniform) olmaması, başlan-gıçta belirlenen günlük dozların çok farklılıklar göster-mesi ve en önemlisi bir grup çalışmada ilave verilecek sıvı miktarı hemodinamik parametrelerle belirlenirken (SVB, PCWB, OAB, KH), diğer çalışmalarda ise belli bir kriter baz alınmaksızın sabit miktar sıvının verildiği hasta gruplarından oluşması tüm bu sonuçların yorumlanmasını güçleştirmektedir.…”
Section: Postoperatif Sıvı Tedavisiunclassified